The "Bright Falx" Sign—Midline Embolic Penetration Is Associated With Faster Resolution of Chronic Subdural Hematoma After Middle Meningeal Artery Embolization: A Case Series. Issue 3 (17th September 2022) - Samarage, Hasitha Milan; Kim, Wi Jin; Zarrin, David; Goel, Keshav; Chin-Hsiu Wang, Anthony; Johnson, Jeremiah; Kaneko, Naoki; Nour, May; Szeder, Viktor; Tateshima, Satoshi; Jahan, Reza; Duckwiler, Gary; et al.
Abstract : BACKGROUND: Chronic subdural hematomas (CSDHs) are common in the elderly population and patients taking antiplatelet/anticoagulation medications. Middle meningeal artery (MMA) embolization has become an adjunctive treatment to observation and surgery. Despite many embolization techniques, best practices for optimal CSDH resolution remain unknown. OBJECTIVE: To report a retrospective case series of MMA embolization for CSDHs regarding rate of hematoma improvement and the significance of distal embolic penetration into the falx. METHODS: Retrospective chart review was performed on all patients who underwent MMA embolization for CSDHs between January 2017 and June 2021. Patient demographics, clinical presentation, anticoagulant use, and radiographic features were collected. Pre-embolization and postembolization computed tomography scans were analyzed for volumetric changes and assessed for midline penetration of embolic material in the falx. RESULTS: MMA embolization was performed in 37 patients and 53 hemispheres. Older patients took longer to obtain complete resolution of CSDHs (r = 0.47, P = .03). Patients with larger pre-embolization (r = 0.57, P = .007) and postembolization (r = 0.56, P = .008) CSDH volumes took longer to completely resolve. Patients who had n-butyl cyanoacrylate embolization with midline penetration, as evidenced by the "bright falx" sign, had faster improvement rates than those who did not (5.64 cm 3 /d vs 1.2 cm 3 /d, P = .02). CONCLUSION: Distal penetration of embolic material, particularly n-butyl cyanoacrylate, into the falx may lead to more rapid improvement of CSDH.